Remaja Berdaya: Menguatkan Kesadaran Pendidikan Seksual Sebagai Perisai Pencegahan HIV dan IMS di Lembaga Pemasyarakatan Anak - Vivi Triana; Muhammad Ilham Basgoro; Adilla Eka Hidayanti; Fadilah Yuma Zahara; Fajriani Dwi Wahyuni; Nur Dinie Assyifa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Class II Special Juvenile Rehabilitation Center (LPA) in Tanjung Pati faces significant challenges in fostering adolescents, mainly due to the lack of knowledge about sexual education. This lack of awareness increases the risk of HIV and Sexually Transmitted Infections (STIs) among LPA residents. To address this issue, more intensive prevention efforts were needed through comprehensive HIV/AIDS education. This community service program aims to enhance the understanding and awareness of adolescents in LPA regarding sexual education, mainly related to HIV/AIDS, as a concrete step in preventing the transmission of these diseases. The partner for this program is the Special Development Institution for Children Class II Tanjung Pati, focusing on male adolescents aged 14-19. The program results positively impacted the overall outcome, significantly increasing participants' understanding scores from pre- to post-intervention. Data analysis confirms that the intervention significantly improved participants' knowledge of HIV and STIs. The program needs continuous training for educators and staff at LPA on sexual education and the development of more comprehensive and integrated HIV prevention programs within the institution. This program not only succeeded in achieving its objectives but also provided hope for strengthening awareness and understanding of the importance of sexual education as a preventive measure against HIV and STIs among adolescents in LPA.